SATISFACTION OF RURAL TOURISTS WITH GREAT PLAIN’S SPAS - Szabó, Zoltán (Acta Carolus Robertus, 2021)
Hungary has a significant tradition in the development of spa tourism. As a result of the developments, a significant number of settlements have qualified baths, which are located in the largest number in the Great Plain. Recently, there are had been barriers to international spa tourism which favoured domestic tourism. It is also characteristic of Hungarians that with the appreciation of health, primarily no longer urban people involved in spa tourism, but increasingly in rural areas. This research examines the satisfaction of the increasing number of rural spa tourists with the quality of the services provided by the spas. The results of the research call attention to the fact that the rural tourists are satisfied with the quality of spa services, but there are factors whose development that must be done without delay in order to spas remain competitive.
Keywords: Consumer satisfaction; spa service; spa tourist; tourism